Case Report: Oral lichenoid mucositis in a patient with metastatic renal cell carcinoma undergoing treatment with pembrolizumab and axitinib - Wellen, Andrew; Pierro, Michael J.; Wanat, Karolyn A.; Nelson, Ariel A. (Frontiers in Oncology, 2025)
Stomatitis is a relatively common adverse effect of systemic pharmacologic therapy seen in the treatment of various malignancies. When severe, stomatitis has the potential to limit a patient’s ability to tolerate optimal medical therapy and to impact quality of life. There are a variety of etiologies underlying stomatitis, including lichenoid drug eruptions. Herein, we present a novel case of a patient with metastatic renal cell carcinoma treated with pembrolizumab and axitinib who subsequently developed stomatitis consistent with a lichenoid drug reaction on biopsy. Pembrolizumab is known to cause such eruptions, and while there are no known lichenoid reactions reported for axitinib, stomatitis is one of the most common adverse effects of this therapy. In our case, it was not clear which systemic agent was the culprit. Axitinib was initially discontinued at the onset of symptoms. However, after a biopsy revealed lichenoid changes that are typically associated with pembrolizumab, pembrolizumab therapy was also stopped. With drug interruption and systemic glucocorticoid therapy, the patient’s stomatitis eventually improved. However, when axitinib was re-introduced to his treatment regimen, the patient experienced severe worsening of his oral lesions and development of new hand lesions requiring hospital admission. While the exact etiology of the lesions is unknown, the timeline of events appears to indicate a potential role of axitinib. This patient case represents a unique clinical scenario of axitinib contributing to a lichenoid drug eruption and highlights the importance of carefully considering the contributions of each agent in multidrug therapy regimens. Such cases are expected to become more frequent as combination immunotherapies and targeted therapies continue to gain approval across multiple solid tumor malignancies.